Actual areas of development of digital competence of officers of the Armed Forces of Ukraine (Educational Dimension, 2021)
The purpose of the study is to find ways to solve the current problem of improving the military education system. The needs in the formation and development of digital competencies of military management officers in different competence areas were studied: information and data literacy, communication and collaboration, digital content creation, safety and problem solving are studied. Possession of a high level of competence in these areas, according to the authors, significantly affects the professional development of officers during their military careers. The attention is focused on the possibility of implementing transdisciplinary integration in the system of advanced training of officers of the Armed Forces of Ukraine. The subject of the study, among other things, was the formation of readiness to use STEM-technologies in professional activities. The study reviewed modern STEM-approaches in the educational process and analyzed the experience of countries such as the United States, Australia, China, Britain, Israel, Korea, Singapore. The results of the survey among the students of advanced training courses at The National Defence University of Ukraine named after Ivan Cherniakhovskyi are highlighted. In particular, the attitude and needs of military management officers to training and professional development were clarified; identified their educational interests. In particular, the need for effective ownership of tools for planning and organizing project work, analysis and evaluation of achieved results is identified.